High-Temperature Creep Buckling Phenomenon of Steel Columns Subjected to Fire. (1st September 2014) - Morovat, Mohammed; Engelhardt, Michael; Helwig, Todd; Taleff, Eric
Abstract : This paper presents highlights of on-going research, which aims at developing analytical, computational and experimental predictions of the phenomenon of creep buckling in steel columns subjected to fire. Analytical solutions using the concept of time-dependent tangent modulus are developed to model time-dependent buckling behavior of steel columns at elevated temperatures. Results from computational creep buckling studies using Abaqus are also presented, and compared with analytical predictions. Material creep data on ASTM A992M steel is also presented and compared to existing creep models for structural steel. Both analytical and computational methods utilize material creep models for structural steel developed by Harmathy, by Fields and Fields, and by the authors. Predictions from this study are also compared against those from Eurocode 3 and the AISC Specification. Results of this work show that neglecting creep effects can lead to erroneous and potentially unsafe predictions of the strength of steel columns subjected to fire.